(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Bioecological characteristics of mulberry (Morus, nigra L) plant species were studied, vegetative reproduction was developed. The use of vegetatively propagated mulberry (Morus, nigra L) species in the landscaping of highways was studied. In the conditions of Uzbekistan, methods of applying mulberry (Morus, nigra L) to scenic greening of highways were developed.